EVALUATION OF HUMAN VISUAL PERCEPTION AND COGNITION TO CHROMATIC STIMULI USING P100/P300 EVENT RELATED POTENTIALS - BEKDASH, MONES (2016)
Colors play an essential role in transport safety research, and the range of colors from bright to dim could be differently discriminated by human, which could affect his/her response to hazard. However, the human visual perception and cognition in response to different colors, vary in luminance level, need to be explored by recording their indications in the electroencephalogram (EEG). Hence, the aim of this study is to identify the effects of changes in color and luminance on human visual perception and cognition process by evaluating the brain event related potentials (ERPs) responses to chromatic stimulation. Twenty (20) healthy subjects with normal or corrected to normal vision and no known color deficiencies are involved in this study. Subjects vary between males and females in age between 20-30 years old. First, the human visual evoked potentials (VEPs) responses are recorded from the brain occipital region using checkerboard stimulus and ensemble averaging technique in order to extract the VEPs peaks (N75, P100, and N135) from the EEG background noise.